(3GdeQCI GdeUQjI GdeYGUQI aj GdHQdeGfs (3fGFHI JaNQ HgG eUQs - (3GdeLdS GdCYdi ddKbGaIs; (3YUahQ, LGHQs ((3GdbGgQIs (3GdeLdS GdCYdi ddKbGaIs, 2009)
(3GdcJGH jJcde Yf eKd eTQa ddeQCI GdeUQjI ai GdSdWI GdJTQjYjI hgi fGFHI ai GdHQdeGf GdeUQi hJbdOJ efGUH YGdejI CNQi MjK jHQR GdcJGH OhQgG GdaYGd ai gPg GdefGUH eOYeG HGdUhQ GdTNUjI ai cd aUds
(3GdeMJhjGJ (B: (3ai eLdS GdTYH(B--(3efGUH HQdeGfjI OhdjI(B--(3eY GdbjGOGJ GdOhdjI(B--(3ehGba hCbhGd eSLdIs
(3jZWi eUQs
Hurg
5 20 22
Keywords: (3eUQs -- (3GdgjFGJ GdJTQjYjIs; (3GdOHdheGSjhfs; (3GdeQCI ai GdSjGSIs; (3GdeQCI aj eUQs; (3GdgjFGJ GdOhdjIs; (3eUQs -- (3eLdS GdTYHs